Experimental study of ground penetrating radar detection and imaging - Wang, Lu (2015)
This project aims to find the possibility of using Synthetic Aperture Radar (SAR) technique for Ground Penetrating Radar to detect the underground structure without destruction. The antennas send the radar signal to the subsurface and make use of the reflected signal to plot the 3-D subsurface image. When the signal encounters to the buried material or the boundary between two types of material of which has different dielectric constant, it will be reflected and collected by the receiver. By scanning 2-D area using the SAR technology, the area position with the depth information will be obtained. By increase the accuracy of positioning, the robotic arm is employed and control by the pre-setup program. The data received is a combination data of area. To obtain the particular point of data, the back projection method is used in the design project. Inverse fast Fourier transform converts the frequency domain to the time domain data. The response time is proportional to the distance signal travelled. The received data is analysis and rearrange to the appropriate format by the Matlab program. The 3-D image is plotted and compared with the real condition had been setup. The concept of Polarimetric Synthetic Aperture Radar (PolSAR) technique has been discussed in this project. Compared with single polarization image, the advantage of composite image will be discussed.